El español en Taiwan - Sun, Ana Su-Ching (Huarte de San Juan. Geografía e Historia, 2006)
Between 50’s and 60’s, first departments of Spanish language were established in Taiwanese universities. They originated as independent departments in the universities of Tamkang, Fu Jen, Providence and Wenzao; however, Spanish teaching is included in the programs of languages departments in other taiwanese universities such as National Taiwan University, National Cheng-Chi University, National Cheng Kung University, National Kaohsiung Normal University, National Kaohsiung University, Central Police University, Chang Jung Christian University or Cheng Shiu Institute of Technology. This article, by examining the activity of the four main Spanish teaching centres of Taiwan, aims, through an aproximation to the state of the art, to point out the important presence of Spanish language in Taiwanese teaching centres.